Metal-Catalyzed Routes to Dibenzodiazepines (DBDAs) and Structural Analogues: Recent Advances - Burke, Anthony (2019)
It is common knowledge that the use of transition metals as catalysts has greatly revolutionized various coupling procedures to access heterocyclic compounds of significant industrial interest. Dibenzodiazepines (DBDAs) are a particularly important group of heterocyclic compounds, with considerable pharmaceutical applications. In this review, we look at some of the catalytic methods that have been developed during the last 10 years for the synthesis of these targets. Palladium catalysts have been frequently used for these transformations, and particularly for the Buchwald-Hartwig reaction which has been a key reaction in a number of synthetic pathways. Copper has also been frequently used, including some other metals like iron and molybdenum, but to a lesser extent. In most cases, the examples chosen are for the synthesis of DBDAs with interesting medicinal properties and will be of interest to medicinal chemists. It should also be mentioned that due to the structural characteristics of these compounds the potential for diversification - principally for functional group incorporation - is immense. Emerging and facilitating technologies have also been employed for the synthesis of these molecules and are reviewed here.